Performance Metrics for Fluidic Soft Robot Rotational Actuators - Rupert, Levi; Saunders, Benjamin O.; Killpack, Marc D. (Frontiers in Robotics and AI, 2021)
The field of soft robotics is continuing to grow as more researchers see the potential for robots3that can safely interact in unmodeled, unstructured, and uncertain environments. However,4in order for the design, integration, and control of soft robotic actuators to develop into a full5engineering methodology, a set of metrics and standards need to be established. This paper6attempts to lay the groundwork for that process by proposing six soft robot actuator metrics that7can be used to evaluate and compare characteristics and performance of soft robot actuators.8Data from eight different soft robot rotational actuators (five distinct designs) was used to evaluate9these soft robot actuator metrics and show their utility. Additionally we provide a simple case10study as an example of how these metrics can be used to evaluate soft robot actuators for a11designated task. While this paper does not claim to present a comprehensive list of all possible12soft robot actuator metrics, the metrics presented can 1) be used to initiate the development and13comparison of soft robot actuators in an engineering framework and 2) start a broader discussion14of which metrics should be standardized in future soft robot actuator research.